2023
DOI: 10.9734/ijecc/2023/v13i11593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IPM Modules against Fall Armyworm in Maize through Frontline Demonstration and Its Economic Impact

Abstract: Aim: The present study was undertaken to assess IPM modules against Fall Armyworm in Maize through Frontline Demonstration and its economic impact. Place and Duration of Study: The present study was carried out in Ananthapuramu district of Andhra Pradesh during the period 2020-2023. Methodology: The main objective of frontline demos is to demonstrate recently available crop production and protection technology, as well as their management practices, in a farmer's field in a micro farming setting. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…The prophylactic spraying of entomopathogenic fungicide like Metarhizium anisopliae @ 5g/L and chemical insecticide like emamectin benzoate 5SG @ 0.4g/L were effective in the management of larvae. Similar findings were observed by Geetha [16], Reddy et al, [17], and Narayanamma et al [18].…”
Section: Resultssupporting
confidence: 90%
“…The prophylactic spraying of entomopathogenic fungicide like Metarhizium anisopliae @ 5g/L and chemical insecticide like emamectin benzoate 5SG @ 0.4g/L were effective in the management of larvae. Similar findings were observed by Geetha [16], Reddy et al, [17], and Narayanamma et al [18].…”
Section: Resultssupporting
confidence: 90%
“…In Andhra Pradesh's tribal regions, a comparable study found that maize yields rose from 62.1-85.3 q/ha. Similar to the current experiment, Reddy et al (2023) [13] found that the benefit cost ratio was much greater in the suggested technology (2.51) related to farmers practice (2.12).…”
Section: Economics Of Ipmsupporting
confidence: 78%
“…Reddy et al . 40 reported that the benefit–cost ratio was significantly higher in the recommended approach (2.51) when compared to the farmer’s practice (2.12). The higher grain output and better market pricing of the produce may be the causes of the maize demonstration's higher net returns and B:C ratio 37 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 40 reported that the benefit–cost ratio was significantly higher in the recommended approach (2.51) when compared to the farmer’s practice (2.12). The higher grain output and better market pricing of the produce may be the causes of the maize demonstration's higher net returns and B:C ratio 37 , 40 . The lower yield in the farmer’s field might be attributed to the use of insecticides, in which FAW known to developed resistance against most of them for instance cypermethrin 16 , lambda cyhalothrin 17 and profenophos 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation